SEDENTARISM IN SCHOOL ADOLESCENTS (Fiep Bulletin - online, 2019)
The WHO understands that the sedentarismo is associated with the daily behavior with low level of physical activity. Inrecent years, there has been a significant increase in the prevalence of sedentary behavior among adolescents (12 to 18 yearsold), not only in Brazil but also in developed countries, which may reach epidemic proportions if there are no public policies aimedat the promotion, prevention and treatment of this condition. Although the effects are not yet great, studies that have been carriedout with the objective of evaluating and measuring sedentary behavior in adolescents have been carried out and have presentedimportant results for the academic community
Keywords: Adolescents; Schoolchildren; Sedentary Lifestyle.